2005
DOI: 10.1364/opex.13.010815
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent characterization of THz Sommerfeld wave propagation on single-wires

Abstract: In this work, measurements and numerical field simulations highlighting the characteristic propagation behavior of THz surface-wave pulses along bare and dielectrically coated metal wires are presented. An optoelectronic time-domain measurement setup with a freely-positionable probe-tip is used for detection of electrical field transients after different propagation lengths along the wires. Frequency-dependent attenuation and dispersion parameters are determined in the range of 0.02 THz to 0.4 THz. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 17 publications
0
39
1
Order By: Relevance
“…These waves are extensively used in THz near-field imaging as shown in Section 2.6. The Aachen group directly studied the field at the wire itself using their PC probe-tip based setup [100] which leads to use tapered wire as near-field probe [10]. The Mittleman group has measured the spatial profile of the electric near-field at the end of a wire where THz waves were propagating.…”
Section: Plasmonics On a Flat Surfacementioning
confidence: 99%
“…These waves are extensively used in THz near-field imaging as shown in Section 2.6. The Aachen group directly studied the field at the wire itself using their PC probe-tip based setup [100] which leads to use tapered wire as near-field probe [10]. The Mittleman group has measured the spatial profile of the electric near-field at the end of a wire where THz waves were propagating.…”
Section: Plasmonics On a Flat Surfacementioning
confidence: 99%
“…The THz pulses propagate on these wires as surface plasmon polaritons having a radial polarization and are often referred to as Sommerfeld waves [3,4]. It has been shown that these pulses can travel relatively long distances of up to a few meters on these wires, since they experience little attenuation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency-domain propagation parameters (not shown here) of the wire have been retrieved from the time-domain data by a procedure described in [55]. Using these freely-positionable PC probetips the frequency-dependent attenuation and dispersion behaviour of Sommerfeld wires was measured in qualitative and quantitative agreement with numerical field simulations [64]. Compared to other approaches, where the field radiated from the end of the waveguide is probed, our method appears to be favorable for waveguide characterization since the field pattern radiated from an open end of a waveguide is highly-frequency dependent [65].…”
Section: Application Examples: Thz Waveguide Probe-tip and Antenna Dmentioning
confidence: 98%
“…The probe-tip has been applied to characterize the propagation properties of THz Sommerfeld wire waveguides by recording the amplitude and phase information of transient electric fields after different propagation distances [64]. For this task, a radial LT-GaAs-based PC antenna, as sketched in Fig.…”
Section: Application Examples: Thz Waveguide Probe-tip and Antenna Dmentioning
confidence: 99%